2009
DOI: 10.1007/s10640-009-9261-0
|View full text |Cite
|
Sign up to set email alerts
|

Asking for Individual or Household Willingness to Pay for Environmental Goods?

Abstract: Contingent valuation, Household, Individual, WTP, Q51, H41,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 30 publications
2
21
1
1
Order By: Relevance
“…Efforts were also made to harmonize questionnaire design between modes as much as practically possible. A random withinhousehold sampling method was chosen for the three modes (the adult person with the ''last birthday'' was chosen), as this may also be a potential source of differences in stated values (Lindhjem and Navrud, 2009). To further isolate measurement effects the samples were weighted to a set of marginal distributions on common demographics (though, importantly, not income), using census benchmarks.…”
Section: Mail Telephone and Computer At Central Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts were also made to harmonize questionnaire design between modes as much as practically possible. A random withinhousehold sampling method was chosen for the three modes (the adult person with the ''last birthday'' was chosen), as this may also be a potential source of differences in stated values (Lindhjem and Navrud, 2009). To further isolate measurement effects the samples were weighted to a set of marginal distributions on common demographics (though, importantly, not income), using census benchmarks.…”
Section: Mail Telephone and Computer At Central Locationmentioning
confidence: 99%
“…A growing number of Internet-based SP studies of environmental goods (even high-budget ones such as Banzhaf et al (2006) that may be considered best practice along other dimensions) have already been published, or are in the pipeline (see, e.g., Tsuge and Washida, 2003;Berrens et al, 2004;Ladenburg and Olsen, 2008;Lindhjem and Navrud, 2009;Cai et al, 2010). While the mass exodus from traditional survey modes to the Internet in SP research is gathering pace, we think it is worth pausing to consider how this new mode may influence the derived SP and welfare measures for environmental goods.…”
Section: Introductionmentioning
confidence: 99%
“…Lackman and Lanasa (1993) indicated that many purchasing decisions of families were not the outcome of an individual choice but influenced to a great extent by other family members. Lindhjem and Navrud (2009) documented that the two primary explanations for why Norwegian households favored environmental goods more than individuals were that incomes of both adults and the partner's opinion were taken into account. As the selection of heating system usually requires a large financial investment, and includes at least two adult members of a household, this decision is defined as a decision taken at a household level for the purpose of further discussion.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The two first columns in (Lindhjem 2007;Lindhjem and Navrud 2008a). It can also be expected that WTP given per month multiplied by 12 to convert to an annual amount is higher than WTP originally stated on an annual basis (a well-known bias).…”
Section: Meta-data From Nature Conservation Studiesmentioning
confidence: 99%